Prevalence and determinants of nasal carriage of penicillin non-susceptible Streptococcus pneumoniae: a cross-sectional household survey in northern VietnamResearch in context - Costanza Tacoli; Hien Anh Thi Nguyen; Tu Cam Thi Nguyen; Bich Ngoc Thi Vu; Max van Wijk; Quynh Dieu Pham; Huong Kieu Thi Tran; Thuong Hong Thi Nguyen; Trang Thu Nguyen; Tung Son Trinh; Dung Tien Viet Vu; Hoang Huy Tran; et al. (The Lancet Regional Health. Western Pacific)
Summary: Background: Beta-lactams remain the first-line treatment of Streptococcus pneumoniae infections despite the increasing global prevalence of penicillin-resistant/non-susceptible strains. We conducted a cross-sectional household survey in a rural community in northern Vietnam in 2018–2019 to provide prevalence estimates of penicillin non-susceptible S. pneumoniae (PNSP) carriage and to investigate behavioural and environmental factors associated with PNSP colonization. The data presented will inform the design of a large trial of population-based interventions targeting inappropriate antibiotic use. Methods: A survey was conducted between July 2018 and April 2019, encompassing 1502 individuals from 324 households. A total of 1, 498 samples from nasal and nasopharyngeal swabs were cultured on blood agar plates supplemented with 5 μg of gentamicin. S. pneumoniae colonies were confirmed by MALDI-TOF. Penicillin susceptibility was tested by E-test. Logistic regression models were used to explore risk factors for PNSP carriage compared to susceptible strains. Findings: We recovered 132 S. pneumoniae isolates out of 1148 swabs. Antibiotic susceptibility results were obtained for 97% (128/132). Of these, 76% (97/128) were PNSP (MIC ≥ 0.12 μg/ml) and 77% (99/128) were non-susceptible to three or more antibiotics. After adjusting for age and wealth, antibiotic use was not associated with PNSP carriage. Participants more likely to be colonized with PNSP were young (≤20-years) and more frequently ate meat and dairy products, particularly pork (adjusted OR 52.30 [95% CI 8.72–313.60]) and milk derivatives (aOR 12.48 [4.01–38.82]). Consumption of fermented food was a protective factor (aOR, 0.02 [<0.01–0.13)]. Interpretation: The prevalence of PNSP was high, but not associated with individual antibiotic use. Community-level interventions to reduce antibiotic consumption are urgently needed, as well as further investigations on antibiotic residues in food products to assess their role in the emergence and prevalence of PNSP. Funding: This work was supported by Oxford University Clinical Research Unit internal grants from the Wellcome Trust Africa Asia Programme core grants (2015-2022—106680/Z/14/Z and 2022-2029—2022-2029—225167/Z/22/Z).